P Pemberdayaan Koperasi Syariah Dalam Ekonomi Umat Sebagai Solusi Resesi Ekonomi (Studi Kasus Di KSPPS Darun Nahdla Kapita) - Dina Apriana -; I Wayan Lasmawan; I Nengah Suastika (Jurnal Istiqro, 2023)
The efforts to improve Islamic-based economic welfare are carried out through Islamic cooperative services. Islamiccooperativecontributes to providing services based on Islamic values to manage financing based on the principle of cooperation based on profit sharing from joint business activities. Business activities carried out in Islamiccooperativeare in the form of accumulating capital from members' savings and loans and used as savings/investments for members. Financial investment can be one of the solutions in dealing with economic recession. This is the aim of this study to describe the management of the Darun Nahdla Capita Islamic cooperative business activities as a business entity that can assist members in improving welfare and overcoming economic problems. This type of research is qualitative, with data collection through observation, interviews, questionnaires, and documentation, the data is then managed through the stages of data collection, data reduction and classification, data presentation, and drawing conclusions. Through this research, it can be described the level of member satisfaction with the very satisfied category both in service and business management and the role or position of the Darun Nahdla Capita Islamic cooperative is very important in helping members improve their welfare. In addition, through the business activities carried out, namely the savings and loan business, it can become a member's financial investment as well as a solution to the economic recession.